Association between fish oil supplementation and cancer risk according to fatty fish consumption: A large prospective population‐based cohort study using UK Biobank. Issue 4 (12th October 2021) - Liu, Zheran; Luo, Yaxin; Ren, Jianjun; Yang, Lianlian; Li, Juejin; Wei, Zhigong; He, Yan; Wang, Jingjing; Li, Ruidan; He, Ling; Mu, Xiaoli; Huang, Yan; et al.
Abstract: Whether regular fish oil supplementation is associated with cancer risk is controversial. We aimed to evaluate the association of fish oil supplementation on cancer risk according to fatty fish consumption patterns. From the UK Biobank cohort, 470 804 participants with fish oil supplementation data were included. A total of 147 316 individuals with fish oil supplementation were in the exposed group; the other 323 488 were in the unexposed group. No association was found between self‐report regular fish oil supplementation and overall cancer risk (hazard ratio [HR] = 0.97, 95% confidence intervals [CIs] = 0.95‐1). Stratified by fatty fish consumption level, we found the association between fish oil supplementation and lower cancer risk in participants who consumed fatty fish less than two times per week, with association noted for both overall cancer (HR = 0.96, 95% CI = 0.94‐0.99) and some specific cancers (colon cancer: HR = 0.84, 95% CI = 0.75‐0.94; hepatobiliary cancer: HR = 0.74, 95% CI = 0.58‐0.96; lung cancer: HR = 0.87, 95% CI = 0.78‐0.98). On the contrary, a higher risk of breast cancer was observed (HR = 1.16, 95% CI = 1.01‐1.32) in participants who consumed fatty fish at least two times per week. In conclusion, our findings underscore the need to refine recommendations for nutritional supplements according to inherent diet habits. Abstract : What's new? Previous evidence from randomised controlled trials and meta‐analyses suggests that fish oil supplementation may not lower overall cancer risk, but the results were largely inconsistent. This large‐scale prospective real‐world analysis of half a million U.K. Biobank participants found that regular fish oil supplementation was not associated with overall cancer risk. When stratifying the participants based on their dietary fish oil consumption, however, regular fish oil supplementation was associated with lower cancer incidence in participants with insufficient dietary fish oil consumption. These findings underscore the need to refine recommendations for fish oil supplementation according to dietary habits.